2015
DOI: 10.1158/1940-6207.capr-15-0141
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Use and Risk of Prostate Cancer: Results from the REDUCE Study

Abstract: The role of metformin in prostate cancer chemoprevention remains unclear. REDUCE, which followed biopsy-negative men with protocol-dictated PSA-independent biopsies at 2- and 4-years, provides an opportunity to evaluate the link between metformin use and prostate cancer diagnosis with minimal confounding from screening biases. In diabetic men from REDUCE, we tested the association between metformin use, use of other anti-diabetic medications, vs. no anti-diabetic medication use and prostate cancer diagnosis as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…In the subgroup of men with T2DM with more than 1 year disease duration, we found no decrease in risk of prostate cancer for men on metformin and a weak decrease in risk for men on insulin/sulfonylurea compared to men with T2DM not on anti‐diabetic drugs. These results are in line with previous studies on metformin in a similar setting …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the subgroup of men with T2DM with more than 1 year disease duration, we found no decrease in risk of prostate cancer for men on metformin and a weak decrease in risk for men on insulin/sulfonylurea compared to men with T2DM not on anti‐diabetic drugs. These results are in line with previous studies on metformin in a similar setting …”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with previous studies on metformin in a similar setting. 11,40 Other studies of men with T2DM have investigated the association between metformin and risk of prostate cancer with other referents than used in our study. One study investigated metformin versus sulfonylurea, 14 one study compared ever-users with never-users of metformin 41 and three metaanalyses looked at metformin versus all other therapies combined.…”
Section: Cancer Epidemiologymentioning
confidence: 99%
“…Interestingly, clinical trial data for metformin, a mitochondrial inhibitor, has shown that African American patients, in general, respond better to this drug than European American patients (20). Metformin was also more effective in reducing the incidence of PCa and the risk of colorectal cancer death in African American patients compared with European American patients (21,22). These findings provide a rationale for evaluating existing mitochondrial drugs to treat tumors from African American patients.…”
Section: Discussionmentioning
confidence: 92%
“…Accordingly, several reports using pharmacological modulators of AMPK as well as genetic knockout of one of the catalytic subunits of AMPK, PRKAA2 , support a tumor suppressive role for AMPK in prostate cancer 7,17,6365 . However, more recent retrospective studies did not find any link between metformin use and decreased cancer risk 6677 . In fact, some studies even suggested that increased metformin use correlated with more aggressive prostate cancers 66,71 .…”
Section: Introductionmentioning
confidence: 89%